2017
DOI: 10.1002/jcph.866
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Treatment Regimens With the PCSK9 Inhibitors Alirocumab and Evolocumab: A Pharmacokinetic and Pharmacodynamic Modeling Approach

Abstract: Alirocumab and evolocumab are 2 human monoclonal antibodies that inhibit the proprotein convertase subtilisin/kexin type 9 (PCSK9). These antibodies can potently lower low-density lipoprotein cholesterol (LDLc) serum concentrations. The aims of this analysis were to develop a pharmacokinetic (PK) and pharmacodynamic (PD) model for both antibodies, to simulate and investigate different dosage and application regimens, and finally, to note the effects on LDLc levels. Alirocumab was clinically studied and approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…34,35 This response is similar for either regimens of alirocumab or evolocumab. 36 Information documenting the interindividual variability in the LDL-C lowering response to PCSK9 inhibition is, however, limited. This is a pertinent issue, in the light of evidence from the SPIRE programme (see Box 1).…”
Section: Monitoring Ldl-c Lowering Responsementioning
confidence: 99%
“…34,35 This response is similar for either regimens of alirocumab or evolocumab. 36 Information documenting the interindividual variability in the LDL-C lowering response to PCSK9 inhibition is, however, limited. This is a pertinent issue, in the light of evidence from the SPIRE programme (see Box 1).…”
Section: Monitoring Ldl-c Lowering Responsementioning
confidence: 99%
“…[38,53,76,156] An evolocumab study using a TMDD model showed that PCSK9 levels were higher in patients treated with statins. [38] This increase in PCSK9 levels may lead to higher target-mediated clearance of anti-PCSK9 mAbs.…”
Section: Influence Of Concomitant Treatmentmentioning
confidence: 99%
“…However, the Michaelis-Menten term has been used in simplified forms. In five studies on clenoliximab [73] (anti CD4), alemtuzumab [74] (anti CD52), cetuximab [27] (anti-EGFR) otelixizumab [75] (anti-CD3) and anti-PCSK9 mAbs (alirocumab and evolocumab) [76] , no linear (endogenous) elimination term was integrated in the model. The absence of first-order elimination term lead to apparent VM and KM values that may be superior than "actual" values.…”
Section: Michaelis-menten Modelmentioning
confidence: 99%
“…Furthermore, it should be noted that dose optimization was only performed for matching exposure and not linked with a pharmacodynamic (PD) model connecting SL and SA exposure with drug efficacy like change in LDL levels or drug toxicity. 43,45,46 Such a PBPK/ PD MIPD decision support system could enable clinicians to individually balance therapy risks and chances. 47,48 However, as recent investigations have shown, those models should also regard the exposure of SL, which had not been recognized for a long time.…”
Section: Discussionmentioning
confidence: 99%